3D printing of piezoelectric barium titanate with high density from milled powders. Issue 15 (December 2020) - Wei, Xiangxia; Liu, Yinhua; Zhao, Dongjie; Ge, Shuzhi Sam
Abstract: Piezoelectric ceramics are essential for electronic industries due to the capabilities of converting mechanical stresses to an electric field, or vice versa. Three-dimensional printing provides the shaping flexibility, however, piezoelectric properties should be further improved. In this work, barium titanate is manufactured by extrusion freeforming derived from milled precursors. The pure tetragonal phase is formed at 950 °C, which is lower than conventionally required temperature for un-milled counterparts. Upon extrusion, a self-supporting green part could be obtained. Moreover, post processing is necessary for the solid-state reaction and particle sintering to achieve dense structures. It is observed that sintered ceramics reach the maximum density of 5.66 g/cm 3 which exhibits excellent piezoelectric and dielectric properties of 420 pC/N and 4380 at 1 kHz, respectively. This printing technique from milled powders is a promising approach to enable the mass production and customization of piezoelectric devices, a cost reduction is therefore foreseen.